Penurunan Defect Leakage Sikat Gigi Elektrik Dengan Six Sigma Dmaic (Studi Kasus PT. PIB) - Hutasoit, Meika Clara Nauli; Irwan, Hery; Sumarya, Edi (LPPM-ITEBA, 2026)
This paper condenses a Six Sigma DMAIC project implemented in an electric toothbrush assembly line at PT PIB, Batam. Baseline January–September 2025 records 967,700 units with 36,281 defects; leakage contributes ≈60% (21,774 units) and becomes the CTQ. Using Pareto, SIPOC, P-Chart, and fishbone, root causes were traced to unstable air pressure at the leakage tester, rubber-seal mismatch, missing controlled oiling at top-seal assembly, and operator variation. Post-implementation (Oct–Dec 2025) DPMO fell from ≈5,356 ppm (≈4σ) to ≈200 ppm (≈5σ), P-Chart points stayed in-control. These results demonstrate DMAIC effectiveness to reduce leakage defects and stabilize process capability.